Combination of remazolam and alfentanil on hemodynamics, postoperative cognitive function, and adverse cardiovascular events in elderly patients undergoing laparoscopic cholecystectomy: a randomized controlled trial - Liu, Chaolei; Li, Jin; He, Junna; Zhang, Jingjing; Bo, Lijun; Yang, Jiaojiao; Ma, Yuan; Qin, Jianzhang; Yang, Yanjie; Sun, Zhangnan (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the effects of a remazolam-alfentanil combination versus a propofol-alfentanil combination on intraoperative hemodynamics, postoperative cognitive function, and cardiovascular adverse events in elderly patients undergoing laparoscopic cholecystectomy.MethodsThis prospective, randomized controlled trial enrolled 116 elderly patients (aged 60–80 years, ASA I–III) undergoing laparoscopic cholecystectomy from January 2022 to June 2023. Patients were randomly assigned (1:1) to receive either remazolam-alfentanil (n = 58) or propofol-alfentanil (n = 58). Primary outcomes included intraoperative hemodynamic parameters (MAP, HR, CO, CI, SVR), cognitive function (MMSE and MoCA scores, and incidence of postoperative delirium [POD]), and incidence of cardiovascular events. Secondary outcomes included recovery times and postoperative VAS and Ramsay scores.ResultsA total of 112 patients (56 per group) completed the study. The remazolam group had significantly shorter times to awakening (10.41 ± 2.09 vs. 12.68 ± 2.73 min), extubation (11.17 ± 2.11 vs. 14.34 ± 2.62 min), and anesthesia duration (22.53 ± 6.66 vs. 28.81 ± 7.05 min) (all P < 0.001). Intraoperatively, the remazolam group showed more stable hemodynamics with higher MAP, HR, CO, and CI (P < 0.05). Postoperative MMSE and MoCA scores were significantly higher on days 3 and 7 (P < 0.05). The incidence of POD at day 7 was significantly lower in the remazolam group (3.6% vs. 16.1%, P = 0.031). The incidence of cardiovascular events was lower in the remazolam group (21.4% vs. 71.4%, P < 0.001), particularly hypotension (7.1% vs. 62.5%) and bradycardia (14.3% vs. 53.6%). VAS and Ramsay scores were also lower at 6 and 12 h postoperatively (P < 0.001).ConclusionThe remazolam-alfentanil combination provided faster recovery, improved hemodynamic stability, better cognitive outcomes, and fewer cardiovascular events than propofol-alfentanil in elderly laparoscopic cholecystectomy patients. While promising, these findings warrant confirmation in larger, multicenter trials.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=210389, Identifier ChiCTR2300077536.